Wear of the enamel by different chemical and mechanical treatments - Calvo Ramírez, Juan Norberto (2019)
Introduction: Microabrasion is described as a procedure performed on tooth enamel in which the use of an acidic agent and an abrasive agent can correct surface chromatic alterations. Some studies show how the parameters of time, number of applications and the pressure exerted influence the amount of enamel removed.Objective: To establish the thickness of tooth enamel removed according to the abrasive capacity of 9 mechanical chemical treatments, using stereomicroscopy. Materials and methods: With the endorsement of the ethics committee of the School of Dentistry of the National University of Colombia, 90 third molars were collected under informed consent and kept stored under the parameters of ISO 11405. Acrylic blocks were fixed the lingual halves of the dental crowns, creating on them flat surfaces by means of series of sandpaper with irrigation and taking impressions with silicone of addition.They were distributed randomly in 9 groups (n 10). Each group was treated for a period of 30 seconds: G1: Opalustre® (Ultradent), G2: Pumice and 37% phosphoric acid (Ultra-Etch®, Ultradent), G3: Pumice, glycerin and phosphoric acid 37 % (Ultra-Etch®, Ultradent), G4: Yellow halo strawberries (Komet), G5: White halo strawberries (Komet), G6: Sof-Lex® discs (3M), yellow color, G7: Sof-Lex discs ® (3M), yellow and light yellow, G8: Sandblasted, and G9: Perfect Margin ultrasonic tips (Acteon). The wear thickness created was measured using a stereo microscope with an increase of 10X. The collected data were analyzed through the Kruskal-Wallis tests (p≤0.05) to compare all groups and the Mann-Whitney U test (p≤0.05) for individual comparisons. Results: Regardless of the treatment performed, all groups presented enamel wear. The highest wear was recorded for the group treated with yellow halo strawberry (122.66 ± 22.64µm) and the lowest wear for the sandblasting group (11.5 ± 2.36µm). There was a statistically significant difference between all groups. Conclusions: Under the limitations of the present study, it can be concluded: The greatest microabrasion in enamel was produced with strawberries of extra-fine grain (yellow halo) and the least wear occurred with sandblasting.